Subgrade Stabilization of Railway Track: Literature Scientometric ‎Analysis (Journal of University of Babylon for Engineering Sciences, 2023)
The material layer where the ballast and sub-ballast layers lie is known as the subgrade. Since the subgrade is a critical component of the track construction and has contributed to track failure and the deterioration of track quality so many of researcher conducted much research on this layer. The purpose of this study is to comprehensively evaluate and depict the current state of research on railway track. Utilizing the VOS viewer software, the analysis was done using the Web of Science website by looking at the prior study conducted on subgrade of rail track. Using the keyword co-occurrence analysis feature, this study looked at the frequency of occurrence of keyword, "subgrade" based on a total of 456 publications with "subgrade" in the keywords, abstract, or title, the search result successfully identified three groups using the cluster analysis method. Citation burst analysis was used in the study to examine the growth trend in the field of subgrade and show how research on railway track has changed over time. In order to more accurately categorize the present state of affairs and upward trend in railway track, this study is distinctive in that it gives the reader complete information on the body of previous research on subgrade investigations. A review of previous studies showed that the stabilization of the subgrade will enhancing engineering qualities, 10% cement content for railway track subgrade was the ideal ratio for some type of soil.